KAJIAN SEMIOTIK DALAM NOVEL NY. TALIS (KISAH MENGENAI MADRAS)KARYA BUDI DARMA - Siti Ekta Budianti (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2020)
This research is backed up by the desire to understand and interpret the semiotic meaning in Ny. Talis (Kisah Mengenai Madras) novel by Budi Darma. The purpose of this study is to describe: (1) hermeneutic code; (2) semantic/semes code; (3) symbolic codes; (4) proaretic code, and; (5) cultural codes in Ny. Talis (Kisah Mengenai Madras) by Budi Darma. The theory used to analyze the data is Roland Barthes' semiotics which focuses on semiotic codes. The approach used is poststructural semiotics by applying heuristic and hermeneutic semiotic reading methods. Research data in the form of dialog quotes, words, sentences, and paragraphs that are related to the focus of research on semiotic codes. research data sources come from Ny. Talis (Kisah Mengenai Madras) by Budi Darma (1996) published by Balai Pustaka.The results of the research and discussion show that the semiotic codes in Ny. Talis (Kisah Mengenai Madras) novel there is a lexias fragment that connects five semiotic codes. Liaison lexias is nothing but the meaning of signification about death and matters related to death. In addition, the reality of life refers to death.